EVALUASI TINGKAT KEMATANGAN TEKNOLOGI INFORMASI MENGGUNAKAN FRAMEWORK COBIT 4.1 PADA INSTANSI PEMERINTAHAN ABC - Joni Saputra; Bambang Soedijono; M. Rudyanto Arief (Universitas Janabadra, 2020)
Information technology (IT) now plays an important role in the performance process of an organization or government agency, particularly in improving services that are efficient, effective and transparent. Implementation of good IT governance will guarantee the transparency, efficiency and effectiveness of an organization or government agency. Seeing the benefits of applying IT for the creation of a governance and information system that is in accordance with the standards, an evaluation of the maturity level of information technology governance in government agencies will be used using COBIT 4.1 in the sub-domains that meet the problems and needs of the government agencies. The results of this measurement are a description of the results of IT governance and the current Information System and the results of recommendations that will be a reference for future improvements so that government agencies become more measurable and better. In this study, the conclusion of the level of maturity in the domain Delivery and support (DS ) DS1 = 2.81, DS4 = 2.56, DS5 = 2.67, DS11 = 2.65, so that the level of maturity at ABC company is at level 2.5 (Defined Process). Keywords: Cobit, Maturity Level